Analisis Perilaku Sosial pada Anak Slow Learner - Eriska Witantri Budiarti; Amalia Oktaviana; Izzatin Kamala (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2021)
Slow learner children are one of the children categorized as children with special needs. Slow learner children have intelligence under normal children in general. This study was conducted to know the social-behavioural characteristics of slow learner children. This study uses a quantitative approach with slow learner children in Bangunsari Village, Purwodadi Subdistrict, Musi Rawas Regency, South Sumatra. The data collection techniques used are observations, interviews, and literature studies with data obtained in the form of descriptions of slow learner children's social behaviour. The data analysis techniques in this study consist of data reduction, data presentation, and conclusion withdrawal. The results showed that the behaviour of slow learner children is almost the same as normal children in general. Activities carried out in life can be well received by people around. But in some moments, he brings up behaviours that are unique and different from their peers.